A novel source material engineered double gate tunnel field effect transistor for radio frequency integrated circuit applications. (9th September 2020) - Dassi, Minaxi; Madan, Jaya; Pandey, Rahul; Sharma, Rajnish
Abstract: Tunnel field effect transistors (TFETs) have proved their potential for many possible electronic circuit applications. However, with the variety of TFET structures being worked upon it has been an unresolved challenge to optimize them for the applications to which they are best suited. In this paper we present a detailed comparative analysis of the linearity distortion and the radiofrequency (RF) performance parameters of a proposed heterojunction Mg2 Si source double gate TFET (HMSDG-TFET) and a conventional homojunction Si source DG-TFET (SSDG-TFET). A source material engineering scheme is utilized to implement a staggered type 2 heterojunction at the source–channel junction by replacing the source material with Mg2 Si (a low band gap material) to enhance the ON current (2.5 × 10 –4 A µ m −1 ), reduce the threshold voltage (0.26 V) and achieve a steeper subthreshold swing (10.05 mV decade −1 ). For linearity and distortion analysis, the figure of merit (FOM)-like higher-order transconductances, second- and third-order voltage intercepts, third-order intercept point, third-order intermodulation distortion, zero crossover point, 1 dB compression point, second-order harmonic distortion, third order harmonic distortion and total harmonic distortion have been examined. To portray the possible application of devices under consideration for RF integrated circuit applications, both structures are investigated for RF FOMs such as power gains, cutoff frequency (fT ), maximum oscillation frequency ( F max ) and admittance parameters. Investigations carried out using a Silvaco ATLAS device simulator tool revealed that with fT approximately three orders higher (0.49 THz) and F max approximately two orders higher (0.9 THz) than that of a SSDG-TFET, the HMSDG-TFET is an appropriate candidate for use in high-frequency, high-linearity, low-distortion and low-power analog/RF applications.